1 .已知 X^2+X-1=0, 求2002X^3+2001X^2 -2003X-2007的值.2. 化简: 2(a-b)^2n *3x(b-a)^2n-2 * 4y(a-b)^3 (n为整数)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 12:22:44
1.已知X^2+X-1=0,求2002X^3+2001X^2-2003X-2007的值.2.化简:2(a-b)^2n*3x(b-a)^2n-2*4y(a-b)^3(n为整数)1.已知X^2+X-1=0
1 .已知 X^2+X-1=0, 求2002X^3+2001X^2 -2003X-2007的值.2. 化简: 2(a-b)^2n *3x(b-a)^2n-2 * 4y(a-b)^3 (n为整数)
1 .已知 X^2+X-1=0, 求2002X^3+2001X^2 -2003X-2007的值.
2. 化简: 2(a-b)^2n *3x(b-a)^2n-2 * 4y(a-b)^3 (n为整数)
1 .已知 X^2+X-1=0, 求2002X^3+2001X^2 -2003X-2007的值.2. 化简: 2(a-b)^2n *3x(b-a)^2n-2 * 4y(a-b)^3 (n为整数)
其中用到x^2=1-X
2002X^3+2001X^2 -2003X-2007
=2002X(1-X)+2001X^2 -2003X-2007
=2002X-2002X^2+2001X^2 -2003X-2007
=-X-X^2-2007
=-1-2007
=-2008
qeaw
1. -2008
2.6*(a-b)^2【x-4y(a-b)】
X^2+X-1=0得X^2+X=1
2002X^3+2001X^2-2003X-2007
=2002X(X^2+X)-x^2-2003x-2007
=2002X-x^2-2003X-2007
=-x^2-x-2007
=-1-2007
=-2008
已知x*x+x-1=0 求x*x*x-2x+11=?
已知x*x+x-1=0求x*x*x-2x+2010的值
已知x*x-3x+1=0求√(x*x+1/x-2)=?
已知x^-x-1=0,求x^4+x^3-x^2-4x+3
已知x^2+x-1=0,求x^3+x^2-x的值
已知2f(x)+f(1/x)=2x x#0 求f(x)
已知:x^2+x+1=0,求:x^2013+x^2012+x^2011的值
已知x^2+x+1=0,求x^1987+x^1988+...+x^2001的值
已知x^2+x+1=0,求代数式x^1991+x^1992+...+x^1999同上!
已知x^2+x+1=0,求x^2004+x^2003+x^2002
已知2f(1/x)+f(x)=x(x不等于0),求f(x).
已知微分方程(x+1)f(x)+(x+2)f'(x)=0,求f'(x)
已知1+x+x^2+x^3=0,求x+x^2+x^3+x^4+x^+x^6+x^7+x^8的值
已知x^25x+1=0,求x^2+x^-2已知x^2×5x+1=0 求x^2+x^-2
已知X^2+X+1=0,求x^2012+X^2011+x^2010+...+x^2+x+1
已知1+x+x^2+x^3=0,求1+X+x^2+x^3+---+x^2008的值
已知x^2+x+1=0,求1+x+x^2+x^3+x^4+.+x^2005的值.
已知x^2+x+1=0,求1+x+x^2+x^3+x^4+.+x^2006的值.